Home town - Kidder, Tracy (New York Random House, Inc., 1999)
" ... Kidder reveals the sheer abundance of life contained within a town's narrow boundaries. Does the kind of small town that many Americans came from, and long for, still exist? Kidder says yes, although not quite in the form we may imagine. A book about civilization in microcosm ..."--Jacket.
Townie -- The morning polka -- A restraining order -- A moral place -- Hands -- Hunting -- Sanctuary -- Too cold for crime -- Tearless, eager and longing eyes -- Plain Miss Smith -- Total, mindless joy -- I could do this stuff -- The witness list -- Public works -- Meaning well -- The caretaker -- The application -- The trial -- Milton -- The farewell sermon -- Willoughby gap -- Karma -- Free at last -- The judge.
Includes bibliographical references (pages [339]-349)
Keywords: Police -- Massachusetts -- Northampton -- Biography; City and town life -- United States -- Case studies; Northampton (Mass.) -- Biography; Northampton (Mass.) -- Social conditions; Northampton (Mass.) -- History